Investigation of supercapacitor electrode performances of phosphorus-doped graphene oxide electrodes in various deep eutectic solvents and symmetric supercapacitor application - Kalkan, Elanur; Arvas, Melih Besir; Yazar, Sibel; Sahin, Yucel (ELSEVIER, 2023)
A one-step preparation method of phosphorus-doped graphene oxide electrode (P-GOE) was used as electrode material for high-performance supercapacitors. Phosphorus-doped graphene oxides were synthesized on pencil graphite electrodes in one step with easy, cheap, and non-toxic chemicals by using the chronoamperometric process. Electrochemical analyses were carried out to examine the capacitive behavior of the electrodes in different deep eutectic solvents (DESs) (choline chloride:ethylene glycol (ChCl:EG), choline chloride:urea (ChCl: U), choline chloride:phenol (ChCl:Ph)). The electrolytes used make research valuable because these electrolytes were environmentally friendly, non-toxic, and inexpensive. Electrodes were analyzed by cyclic voltammetry at different scan rates, charge-discharge test at different current densities, 1000-cycle galvanostatic charge-discharge test, and electrochemical impedance spectroscopy (EIS). Structural and morphological properties of the electrodes were investigated by FTIR, XRD, SEM, BET, and XPS. As a result of the characterization and electrochemical analysis, it was seen that the phosphorus doping to the electrodes were carried out successfully. The maximum areal capacitances of phosphorus-doped graphene oxide electrodes were calculated to be 450 mF. cm(-2), 140 mF.cm(-2), and 400 mF.cm(-2) in electrolytes for supercapacitor applications. In this study, high-performance P-doped graphene oxide electrodes were produced with an easy method using inexpensive and non-toxic solvents, providing an important contribution as environmentally friendly and sustainable electrode materials for supercapacitor applications.
Keywords: Energy storage systems; Supercapacitor; Graphene oxide; Phosphorus-doped graphene; Deep eutectic solvent; ALL-SOLID-STATE; HIGH-ENERGY DENSITY; CHOLINE-CHLORIDE; PHYSICOCHEMICAL PROPERTIES; RECHARGEABLE BATTERIES; CYCLIC VOLTAMMETRY; CARBON NANOTUBE; BINARY-MIXTURES; ANODE MATERIALS; NITROGEN; Energy & Fuels